Maternal elevated inflammation impairs placental fatty acids β-oxidation in women with gestational diabetes mellitus - Visiedo, Francisco; Vázquez-Fonseca, Luis; Ábalos-Martínez, Jessica; Broullón-Molanes, J. Román; Quintero-Prado, Rocío; Mateos, Rosa María; Bugatto, Fernando (Frontiers in Endocrinology, 2023)
Introduction An adverse proinflammatory milieu contributes to abnormal cellular energy metabolism response. Gestational diabetes mellitus (GDM) is closely related to an altered maternal inflammatory status. However, its role on lipid metabolism regulation in human placenta has not yet been assessed. The aim of this study was to examine the impact of maternal circulating inflammatory mediators ([TNF]-α, [IL]-6, and Leptin) on placental fatty acid metabolism in GDM pregnancies. Methods Fasting maternal blood and placental tissues were collected at term deliveries from 37 pregnant women (17 control and 20 GDM). Molecular approach techniques as radiolabeled lipid tracers, ELISAs, immunohistochemistry and multianalyte immunoassay quantitative analysis, were used to quantify serum inflammatory factors’ levels, to measure lipid metabolic parameters in placental villous samples (mitochondrial fatty acid oxidation [FAO] rate and lipid content [Triglycerides]), and to analyze their possible relationships. The effect of potential candidate cytokines on fatty acid metabolism in ex vivo placental explants culture following C-section a term was also examined. Results Maternal serum IL-6, TNF-α and leptin levels were significantly increased in GDM patients compared with control pregnant women (9,9±4,5 vs. 3,00±1,7; 4,5±2,8 vs. 2,1±1,3; and 10026,7±5628,8 vs. 5360,2±2499,9 pg/ml, respectively). Placental FAO capacity was significantly diminished (~30%; p<0.01), whereas triglyceride levels were three-fold higher (p<0.01) in full-term GDM placentas. Uniquely the maternal IL-6 levels showed an inverse and positive correlation with the ability to oxidize fatty acids and triglyceride amount in placenta, respectively (r= -0,602, p=0.005; r= 0,707, p=0.001). Additionally, an inverse correlation between placental FAO and triglycerides was also found (r=-0.683; p=0.001). Interestingly, we ex vivo demonstrated by using placental explant cultures that a prolonged exposure with IL-6 (10 ng/mL) resulted in a decline in the fatty acid oxidation rate (~25%; p=0.001), along to acute increase (2-fold times) in triglycerides accumulation (p=0.001), and in lipid neutral and lipid droplets deposits. Conclusions Enhanced maternal proinflammatory cytokines levels (essentially IL-6) is closely associated with an altered placental fatty acid metabolism in pregnancies with GDM, which may interfere with adequate delivery of maternal fat across the placenta to the fetus.